Dietary Acrylamide Exposure and Risk of Site-Specific Cancer: A Systematic Review and Dose-Response Meta-Analysis of Epidemiological Studies - Filippini, Tommaso; Halldorsson, Thorhallur I.; Capitão, Carolina; Martins, Raquel; Giannakou, Konstantinos; Hogervorst, Janneke; Vinceti, Marco; Åkesson, Agneta; Leander, Karin; Katsonouri, Andromachi; Santos, Osvaldo; Virgolino, Ana; et al. (Frontiers in Nutrition, 2022)
Diet is a main source of acrylamide exposure to humans. Existing observational data on the relationship between dietary exposure to acrylamide and risk of cancer are inconsistent. We performed a systematic review and dose-response meta-analysis of epidemiological studies evaluating the association between dietary acrylamide exposure and several site-specific cancer. A systematic literature search was conducted in PubMed, Scopus, and Web of Science databases until May 27, 2021. Studies were eligible if they were carried out in non-occupationally exposed adults, assessed dietary acrylamide exposure (μg/day) and reported risk estimates of cancer incidence (all but gynecological cancers). Using a random-effects model, we performed a meta-analysis of site-specific cancer risk comparing the highest versus lowest category of dietary acrylamide exposure. We also carried out a one-stage dose-response meta-analysis assessing the shape of the association. Out of 1,910 papers screened, 31 were eligible, which included 1,151,189 participants in total, out of whom 48,175 developed cancer during the median follow-up period of 14.9 years (range 7.3-33.9). The mean estimated dose of dietary acrylamide across studies was 23 µg/day. Pooled analysis showed no association between the highest vs lowest dietary acrylamide exposure and each site-specific cancer investigated, with no evidence of thresholds in the dose-response meta-analysis. There were also no associations between dietary acrylamide exposure and the risk of cancers when stratifying by smoking status, except for increased risk of lung cancer in smokers. In conclusion, high dietary acrylamide exposure was not associated with an increased risk of site-specific non-gynecological cancer.